Implementace prvků automatizace do výrobního procesu v Poclain Hydraulics s.r.o. - Ciba, Martin (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Cieľom práce je zanalyzovať aktuálny výrobný proces dráh pre hydraulické motory a navrhnúť jeho optimalizáciu. Na základe analýzy výrobného procesu a prieskumu dostupných možností automatizácie sú vytvorené viaceré návrhy automatizovanej výrobnej bunky. Práca sa zaoberá technicko-ekonomickou analýzou projektu a porovnáva viaceré možnosti automatizácie výroby.

The objective of this work is to analyze the current production process of the cams within Poclain Hydraulics and to propose its optimizations. After that, a market research of the possibilities of automation is done. Based on the analysis of the production process and the market research, various configurations of an automated production cell are to be proposed. This work deals with a technical and economic analysis of the problem and compares the different possibilities of automation of the production.
Implementation of automation elements within machining processes in Poclain Hydraulics s.r.o.
Keywords: Automatizácia; robotizácia; výrobná bunka; investičná analýza; Automation; robotization; production cell; investment analysis